2018
DOI: 10.1007/s40744-018-0095-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Patterns for Golimumab and Concomitant Medications in Japanese Rheumatoid Arthritis Patients

Abstract: Janssen Pharmaceutical K.K. and Mitsubishi Tanabe Pharma Corporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…In the present study, concomitant use of oral corticosteroids was associated with a lower response to GLM at 24 weeks. Our previous analysis of this PMS dataset demonstrated that disease activity was higher in patients who were using concomitant oral corticosteroids [19]. Therefore, concomitant use of oral corticosteroids is more likely to be a consequence rather than a cause of failure to control disease activity with GLM.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the present study, concomitant use of oral corticosteroids was associated with a lower response to GLM at 24 weeks. Our previous analysis of this PMS dataset demonstrated that disease activity was higher in patients who were using concomitant oral corticosteroids [19]. Therefore, concomitant use of oral corticosteroids is more likely to be a consequence rather than a cause of failure to control disease activity with GLM.…”
Section: Discussionmentioning
confidence: 89%
“…In the previous GO-AFTER trial, among patients who discontinued prior anti-TNF therapy, those who received GLM at 100 mg appeared to show a numerically higher response than those who received GLM at 50 mg [7]. Additionally, our previous post-hoc analysis of PMS data suggested that physicians are more likely to select 100 mg of GLM for patients who failed previous bDMARD therapy in real-world daily practice [19]. However, there has been no evidence as to the effectiveness of GLM at 100 mg compared with 50 mg in RA patients stratified by the number of previous biologic agents.…”
Section: Discussionmentioning
confidence: 93%
“…As for the effectiveness of bDMARDs in elderly patients, ABT was well tolerated and similarly efficacious in both of the non-elderly (<65 years) and elderly (≥65 years) RA patients [25]. In addition, from the post hoc analysis of post-marketing surveillance in Japan, GLM showed comparable improvement of disease activity between younger (<75 years) and elderly (≥75 years) patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the GO-FORTH study, 9 out of 86 subjects who initiated GLM at a dose of 50 mg underwent dose escalation to 100 mg as rescue treatment because of lack of efficacy, resulting in subsequent improvement of the signs and symptoms of RA [4]. In real-world daily practice, dose escalation of GLM seems to achieve better control in RA patients with higher disease activity [9]. However, dose escalation of biologic agents needs to be carefully appraised since this approach can lead to higher medical costs [10] that impose a greater burden on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%